KAJIAN PELAYANAN PAS BANDARA DI PERSEROAN TERBATAS (PT). ANGKASA PURA I BANDAR UDARA INTERNASIONAL AHMAD YANI SEMARANG - Reynaldi Rizqi M; Sri Suwitri; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
PT. Angkasa Pura I (persero) is the government agency in charge of all matters relating to the licensing arrangement. It’s manifestation and implementation of one – stop service where licensing service was held at one place which include various types of services that have relevance licensing process and served through the door.Purpose of this study is to describe, analyze pas service and identify factors inhibiting airport pas service. The research uses a qualitative description type, because it’s more appropriate to use a qualitative approach to examine the process not the outcome or product. As for the selection of informants basis using purpossive sampling technique with specific consideration. This study uses five dimensions, competence, reability, communication, assurance, understanding the customer.Research results with respect to several factors such as skill in serving prospective applicant’s officers, service assurance that’s pretty good, a lack of communication between employees with prospective aplicants, because the Angkasa Pura only provide information about airport pas service to employees, pas shareholder, and prospective applicants only, so that the Angkasa Pura needs to do publicity by adding a banner that contains about airport pas service at airport services department, so that potential applicants aren’t confused to get services. It can be conclude the Pas service airport service in the company at PT. Angkasa Pura I (persero) Ahmad Yani International Airport Semarang is good enough.